Biocontrol Potential of Bacillus velezensis RS65 Against Phytophthora infestans: A Sustainable Strategy for Managing Tomato Late Blight - Hasna Elhjouji; Redouan Qessaoui; Hafsa Houmairi; Khadija Dari; Bouchaib Bencharki; El Hassan Mayad; Hinde Aassila (Microorganisms)
This study aimed to investigate the biocontrol activity of rhizosphere isolates against late blight disease of tomatoes caused by the fungus Phytophthora infestans. A total of 30 rhizospheric bacterial isolates were evaluated for their antagonistic activity against P. infestans in vitro and in vivo. The results demonstrated that among the 30 isolates tested, six (RS65, RP6, RS47, RS46, RP2, and RS61) exhibited a highly significant inhibitory effect (p < 0.001) on the mycelial growth of P. infestans in vitro, with the inhibition rate exceeding 67%. Among the isolates, RS65 exhibited the highest inhibition rate at 78.48%. For antagonistic mechanisms, the results demonstrated that the six isolates exhibited significant enzymatic activity, including proteolytic, lipolytic, and chitinolytic activity, as well as the production of HCN, cellulase, and pectinase. Isolate RS65, which showed the highest inhibition rate, was further evaluated under greenhouse conditions. This investigation revealed significant differences in the severity of late blight between the control and the RS65 treatment. The control showed a severity level of 31.26%, whereas the RS65 treatment achieved the lowest severity of 16.54%. Molecular identification results indicated that the RS65 isolate (accession numbers PV208381) is a Bacillus genus with 99% proximity to Bacillus velezensis. This finding suggests that the Bacillus RS65 treatment could provide effective protection against P. infestans infection in tomato plants. These findings highlight the potential of Bacillus RS65 as a biocontrol agent in integrated disease management for tomato late blight.